MINERALOGY, GEOCHEMISTRY AND ORIGIN OF SKARN MINERALIZATION ASSOCIATED WITH THE BATU HIJAU PORPHYRY COPPER-GOLD DEPOSIT, SUMABAWA ISLAND, INDONESIA - , May Thwe Aye ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The copper-gold skarn mineralization occurred at the Batu Hijau deposit, a world class porphyry copper-gold deposit, is located in the southwestern corner of Sumbawa Island, Indonesia. The deposit mainly consists of three major rock types: andesitic volcaniclastic unit (Early to Middle Miocene) and equigranular quartz diorite (Late Miocene to Middle Pliocene), which are intruded by the three phases of copper-gold bearing tonalite porphyries (Early to Middle Pliocene). The tonalite porphyries were emplaced along the lithological contacts of two pre-mineralization wall rocks. Skarn were newly found at the contact of calcium rich andesitic volcanic layer and intermediate tonalite porphyry intrusion. Skarn can be classified as calcic-exoskarn, and it consists of a Fe-rich and oxidized skarn locally controlled by faults and fractures. Although no limestone is known in the Batu Hijau deposit, Ca-rich volcanic host rocks favoring to become skarn alteration within the Batu Hijau deposit. Based on the mineral assemblages, the skarn forming process can be divided into two major stages such as prograde and retrograde stages consisting of four sub-stages. Prograde skarn consists of clinopyroxene (diopside) and garnet (mainly andradite) Â± magnetite formed at relatively high fO2 and fS2 and temperature of 340 Ì-515 ÌC while retrograde skarn alteration is dominated by Ferich minerals such as amphibole and epidote formed at lower fO2 and fS2 , temperature down to 200 Ì-396 ÌC. Opaque minerals include chalcopyrite, pyrite, sphalertite, minor galena and bismuth-telluride. Gold precipitates in the retrograde alteration associated bismuth-telluride minerals. A decrease in SiO2 corresponds to increase FeOt from porphyry intrusion towards skarn zones. CaO and FeOt behave comparably in the skarns suggesting that the ore mineralization is coincident with carbonization of prograde assemblages during retrograde alteration. Chemical analysis shows the concentration of gold mineralization of 4.15 g/t and 2.7 g/t from the high grade ore zone. Based on the result of fluid inclusion and Î´34S value, the evolution of fluid origin can be suggested that the origin of skarn and porphyry from the Batu Hijau deposit was largely of an igneous sulfur source of magmatic origin caused by the early anhydrous skarn assemblage is dominated by denser and more saline, and has very high temperature and salinity. The Batu Hijau deposit evidently shows a porphyry-related skarn mineralization that is mineralogically and metallogenically zoned and that transition from one style to the next can be relatively rapid. The result of this research has indicated that the range of porphyry-related deposits, skarn (calc-silicate-magnetite rocks) and porphyry (potassic altered rocks) can form during a single prolonged hydrothermal event